The political thought of Karl Popper - Shearmur, Jeremy, 1948- (Routledge, 1996)
The Political Thought of Karl Popper offers a controversial treatment of Popper's ideas about politics, informed by Shearmur's personal knowledge of Popper together with research on unpublished material in the Popper archive at the Hoover Institute. While sympathetic to Popper's overall approach, Shearmur offers criticism of some of his ideas and suggests that political conclusions should be drawn from Popper's ideas which differ from Popper's own views. Shearmur introduces Popper's political ideas by way of a discussion of their development, which draws upon archive material. He t.